QC LDPC Codes for MIMO and Cooperative Networks using Two Way Normalized Min-Sum Decoding - Waheed Ullah; Yang Fengfan; Abid Yahya (Institute of Advanced Engineering and Science, 2014)
This paper is based on the magnitude overestimation correction of the variable message by using two normalized factors in each iteration for LDPC min-sum decoding algorithm. The variable message is modified with a normalized factor when there is a sign change and with another normalized factor when there is no sign change during any two consecutive iterations. This paper incorporates QC LDPC codes using this new decoding algorithm for flat fading multiple input multiple output (MIMO) channel and single relay cooperative communication networks for improving the bit error performance. MIMO flat fading channel is used with zero forcing (ZF) spatial decoding for noise suppression. The performance is greatly enhanced by using the new min-sum algorithm for medium and short length Cooperative communication network and MIMO LDPC codes.